Genetic Identification of Orientobilharzia turkestanicum from Sheep Isolates in Iran - Tabaripour, Reza; Youssefi, Mohammad Reza; Tabaripour, Rabeeh (Iranian journal of parasitology, 2015)
Adult worms of Orientobilharzia turkestanicum live in the portal veins, or intestinal veins of cattle, sheep, goat and many other mammals causing orientobilharziasis. Orientobilharziasis causes significant economic losses to livestock industry of Iran. However, there is limited information about genotypes of O. turkestanicum in Iran. In this study, 30 isolates of O. turkestanicum obtained from sheep were characterized by sequencing mitochondrial cytochrome c oxidase subunit 1 (cox1) and nicotinamide adenine dinucleotide dehydrogenase subunit 1 (nad1) gene. The mitochondrial cox1 and nad1 DNA were amplified by polymerase chain reaction (PCR) and then sequenced and compared with O. turkestanicum and that of other members of the Schistosomatidae available in Gen-Bank(™). Phylogenetic relationships between them were re-constructed using the maximum parsimony method. Phylogenetic analyses done in present study placed O. turkestanicum within the Schistosoma genus, and indicates that O. turkestanicum was phylogenetically closer to the African schistosome group than to the Asian schistosome group. Comparison of nad1 and cox1 sequences of O. turkestanicum obtained in this study with corresponding sequences available in Genbank(™) revealed some sequence variations and provided evidence for presence of microvarients in Iran.